Expression and Functional Studies of INS-5, an Insulinase-Like Protein in Cryptosporidium parvum - Ni, Ni; Jia, Ruilian; Guo, Yaqiong; Li, Na; Wu, Haizhen; Feng, Yaoyu; Xiao, Lihua (Frontiers in Microbiology, 2020)
The small Cryptosporidium genome (∼9 Mb) has over 20 copies of genes encoding insulinase-like proteases (INS), suggesting that these enzymes may have important biological functions in the pathogen and could be developmentally regulated. In this study, INS-5, a unique member of the INS family in Cryptosporidium parvum, was cloned and expressed in Escherichia coli BL21 (DE3). In addition to the predicted INS-5 of ∼78 kDa, smaller fragments of ∼70, ∼55, and ∼30 kDa were simultaneously generated. After purification through a nickel-nitrilotriacetic acid affinity column, the full recombinant protein obtained was used to prepare polyclonal antibodies. Antibodies raised against INS-5 recognized the recombinant protein and native protein in sporozoite extracts. Further characterization of INS-5 included qRT-PCR assessment of gene expression; immunofluorescence localization of the protein expression in sporozoites, merozoites, and other developmental stages; and neutralization of invasion of C. parvum in vitro. The results obtained indicated that although INS-5 was expressed in sporozoites and merozoites, the high gene expression was from 36 to 48 h of the in vitro culture after invasion. Anti-INS-5 antibodies partially neutralized the invasion (inhibition rate = 38.5%). Results of this study suggest that INS-5 plays some role in the invasion and growth of C. parvum.